Not a waste: Wastewater surveillance to enhance public health - Gitter, Anna; Oghuan, Jeremiah; Godbole, Anuja Rajendra; Chavarria, Carlos A.; Monserrat, Carlos; Hu, Tao; Wang, Yun; Maresso, Anthony W.; Hanson, Blake M.; Mena, Kristina D.; Wu, Fuqing (Frontiers in Chemical Engineering, 2023)
Domestic wastewater, when collected and evaluated appropriately, can provide valuable health-related information for a community. As a relatively unbiased and noninvasive approach, wastewater surveillance may complement current practices towards mitigating risks and protecting population health. Spurred by the COVID-19 pandemic, wastewater programs are now widely implemented to monitor viral infection trends in sewersheds and inform public health decision-making. This review summarizes recent developments in wastewater-based epidemiology for detecting and monitoring communicable infectious diseases, dissemination of antimicrobial resistance, and illicit drug consumption. Wastewater surveillance, a quickly advancing frontier in environmental science, is becoming a new tool to enhance public health, improve disease prevention, and respond to future epidemics and pandemics.